215k views
4 votes
in the expression of (x + 1)^n, the coefficient of the x^3 term is two times the coefficient of the x^2 term. Find the value of n.

User Lafras
by
5.0k points

2 Answers

4 votes

Recall the binomial theorem:


(a+b)^n=\displaystyle\sum_(k=0)^n\binom nk a^k b^(n-k)

where


\dbinom nk=(n!)/(k!(n-k)!)

is the binomial coefficient. So


(x+1)^n=\displaystyle\sum_(k=0)^n\binom nk x^k

The x² term occurs for k = 2, which has coefficient


\dbinom n2=(n!)/(2!(n-2)!)=\frac{n(n-1)}2

The x³ occurs for k = 3, with coefficient


\dbinom n3=(n!)/(3!(n-3)!)=\frac{n(n-1)(n-2)}6

The latter coefficient is twice the other one, so that


\frac{n(n-1)(n-2)}6=2\cdot\frac{n(n-1)}2

Solve for n :


\frac{n(n-1)(n-2)}6=n(n-1)


n(n-1)(n-2)=6n(n-1)


n-2=6


\boxed{n=8}

User Teka
by
5.1k points
4 votes

According to Khayyam-Pascal triangle ,

the value of n is 8.


look \: \\ \\ {(x + 1)}^(8) = {x}^(8) + 8 {x}^(7) + 28 {x}^(6) + 56 {x}^(5) + 70 {x}^(4) + 56 {x}^(3) + 28 {x}^(2) + 8x + 1 \\ (56)/(28) = 2

User RahulKumarShaw
by
5.6k points